Is bigger better? Metropolitan area population, access, activity participation, and subjective well-being - Eric A. Morris; Andrew Mondschein; Evelyn Blumenberg (Journal of Transport and Land Use)
Researchers have posited that larger, denser metropolitan areas have important consumption advantages. We examine this using Cragg two-part hurdle and ordinary least square (OLS) regression models employing data from the American Time Use Survey. We test whether: 1) large metropolitan area residents participate in more out-of-home activities because these activities are more plentiful, richer, and/or easier to access, 2) large metropolitan areas have lower travel times because of higher densities, and 3) activities in larger metropolitan areas have more positive associations with subjective well-being than those in smaller places. We reject all three hypotheses. Metropolitan area population size is largely unrelated to time spent outside the home, excluding travel. Large-metropolitan-area residents participate in more arts and entertainment activities and eat and drink out more often, but they socialize, volunteer, and care for others outside the home less. Larger metropolitan areas are associated with dramatically more travel time. We find no evidence that large metropolitan area activities contribute any more or less to life satisfaction or affect than activities in smaller places. We also find that life satisfaction does not covary with metropolitan area size. In sum, living in a large metropolitan area may primarily involve a tradeoff of (travel) time for money (higher wages), with little net change in welfare.